2014
DOI: 10.1002/pd.4386
|View full text |Cite
|
Sign up to set email alerts
|

Potential first trimester metabolomic biomarkers of abnormal birth weight in healthy pregnancies

Abstract: Serum fingerprinting in early pregnancy can predict the risk of macrosomia. Serum levels of A-FABP and several lipids are promising prognostic markers for macrosomia in healthy pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 48 publications
(57 reference statements)
1
28
0
Order By: Relevance
“…Few existing studies have investigated associations between maternal pregnancy metabolites and newborn size [9,10] and none have examined maternal metabolite profiles post glucose load or evaluated the relationship between maternal metabolites and newborn adiposity or cord C-peptide. A Spanish cohort of 800 mother-newborn pairs related maternal urinary metabolites during pregnancy with fetal and newborn size and similarly found that maternal urinary BCAAs, alanine, steroid hormones and choline were associated with greater intrauterine fetal growth and birthweight [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few existing studies have investigated associations between maternal pregnancy metabolites and newborn size [9,10] and none have examined maternal metabolite profiles post glucose load or evaluated the relationship between maternal metabolites and newborn adiposity or cord C-peptide. A Spanish cohort of 800 mother-newborn pairs related maternal urinary metabolites during pregnancy with fetal and newborn size and similarly found that maternal urinary BCAAs, alanine, steroid hormones and choline were associated with greater intrauterine fetal growth and birthweight [9].…”
Section: Discussionmentioning
confidence: 99%
“…In adults, branched-chain amino acids (BCAAs), aromatic amino acids (AAAs), short-chain acylcarnitines (C2, C6, C8; see ESM Table 1 for acylcarnitine nomenclature) and the carnitine ester of 3-hydroxybutyrate (acylcarnitine C4-OH) have all been associated with insulin resistance, higher HbA 1c and/or postprandial glucose levels [5][6][7][8]. However, the impact of the maternal metabolome on the developing fetus, as evidenced by newborn outcomes, is largely unknown and understudied [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, increased maternal glycerol in the first trimester predicts subsequent pre-eclampsia (107), while lower levels of phospholipids, lysolipids, monoacylglyerols and FA binding protein predict fetal macrosomia (105). Small for gestational age (SGA) can be predicted by a panel of maternal metabolites assayed at 15 weeks of pregnancy, including sphingolipids, phospholipids, and carnitines (108).…”
Section: The Lipid Metabolomementioning
confidence: 99%
“…Mothers with poor pregnancy outcomes showed differences in plasma levels during the second trimester of pregnancy in lipids (sterols, glycerophospholipids, sphingolipids), steroid hormones (progesterone metabolites) and vitamin D metabolites compared to controls (n=40) (23). Another recent study using LC-MS on maternal serum in early pregnancy (12–14th weeks) could predict the risk for birthweight >4000 g (n=20) but not LBW (n=19) (24). Mechanistic insights were provided based on lower levels of phospholipids, lysophospholipids, and monoacylglycerols early in pregnancy in mothers with fetal macrosomia, suggesting an increased transport of lipids to the fetus (also supported by an indirect correlation between placental lipid transporters adipocyte fatty acid-binding protein and maternal free lipids).…”
Section: Applications Of Metabolic Profilingmentioning
confidence: 99%